The impact of pleometric training on the strength characterized by speed and some basic skills of u15 handball players Field study on the level of the province of chlef - مداح رشيد (sports creativity, 2025)
This studyaims to show the role played by the plyometric training method and its impact on certain basic techniques,as well as on the development of strength characterized by speed in handball playersu15. The researcher used an experimental program adapted to the nature of the study. The research community is made up of handball players from the chlefwilaya, The randomly selected research sample is composed of 20 players from the Boukadir team under 15, divided into two groups. The first group the first group followed the plyometric training method and the second group followed the regular training method. In order to analyze the results of the study the researcher used the S.P.S.S V25 analysis program.